Perception of Teachers towards School Principal as Instructional Leader - Dahal, Hikmat (Nepal Journal of Multidisciplinary Research, 2020)
The title of the article is 'Perception of Teachers towards School Principal as Instructional Leader'. Instructional leadership has become one of the most widely researched topics. This type of leadership has been connected to teacher growth and development, teacher job satisfaction, student achievement, and improving school climate in general. The objective of the study included to determine the role played by principals as instructional leaders in schools through the perceptions of teachers. To achieve this purpose quantitative research methodology was used and the study was survey type in nature. The sample consisted of 436 school teachers of Kathmandu district. A self developed questionnaire was developed using Google Forms and sent to the respondents via email and social networking sites. The data were collected from teachers in emails and social media. The data were analyzed by using different descriptive and inferential statistics. Findings of the study indicated that school principals support creativity, innovation and practice of new skills in the classroom. They also praised to those teachers who use creativity in classrooms to enhance the learning of students. They held meetings with teachers to discuss the students’ performance and solve the problems of teachers as an instructional leaders. The findings suggested that there is no significant difference on perception of instructional leadership of principals on the basis of gender of teachers and subjects they teach but have a significant difference on perception on the basis of their academic qualification. It is recommended that principals may be trained that they can use new innovative methods and ideas to discuss with teachers and they help out the teachers to make the dull topics interesting. Principals may motivate teachers by giving different incentives in the shape of awards for bringing innovation in school.